Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Guru Di Era Digital - Rendy Oktavianus Sumarauw; Dameria Sinaga (Educatio, 2025)
The purpose of this study is to evaluate the impact of motivation and work discipline on teacher performance in the digital era. The methodology applied in this study uses a quantitative approach with a survey-based design. The number of participants in this study included 30 teachers, consisting of 25 female teachers and 5 male teachers, who came from an elementary school in SDK Tunas Bangsa Depok. Data collection was carried out through a questionnaire that assessed the variables of motivation, work discipline, and performance of teachers. The data analysis process was carried out using descriptive analysis, Pearson correlation testing, and multiple linear regression. The results of the study illustrate that motivation has a significant positive impact on teacher performance (r = 0.65, p < 0.01), while work discipline also shows a significant positive influence (r = 0.58, p < 0.01). The regression model showed that motivation and work discipline together explained 52% of the variation in teacher performance (R² = 0.52). These findings emphasize the importance of developing motivation and work discipline to improve teacher performance, especially in the digital era which requires adjustments and innovations in the learning process.